2018
DOI: 10.1186/s12957-018-1485-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thyroid cancer risk in more than 334,000 patients with inflammatory bowel disease: a case-control study and a meta-analysis

Abstract: BackgroundPotential risk of thyroid cancer in patients with inflammatory bowel disease has not been well investigated. The aim of the study was to reveal the relationship between history of inflammatory bowel disease and risk of thyroid cancer.MethodsFirst, 1392 patients with inflammatory bowel disease and 1392 controls were included in a case-control study. All patients did not receive immunosuppressive therapy. A multivariate logistic regression analysis was adopted to determine the relationship between hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Our results are in line with those described in a US large investigation which have reported that CD, not UC, was associated with a high risk of thyroid cancer [20]. On the contrary, a recent meta-analysis reported that patients with UC had an increased risk of thyroid cancer, while patients with CD did not [23]. It is possible that the inflammatory response of IBD itself and the use of immunosuppressants may contribute to the development of thyroid cancer.…”
Section: Plos Onesupporting
confidence: 92%
“…Our results are in line with those described in a US large investigation which have reported that CD, not UC, was associated with a high risk of thyroid cancer [20]. On the contrary, a recent meta-analysis reported that patients with UC had an increased risk of thyroid cancer, while patients with CD did not [23]. It is possible that the inflammatory response of IBD itself and the use of immunosuppressants may contribute to the development of thyroid cancer.…”
Section: Plos Onesupporting
confidence: 92%
“…The included meta-analyses were published in English between 2014 and 2019. Various disease outcomes included cancers (n=7) [26][27][28][29][30][31], cardiovascular and cerebrovascular diseases (n=8) [32][33][34][35], obstetrical diseases (n=4) [36], neuropsychiatric disease (n=1) [38], otolaryngology and stomatology diseases (n=2) [41,43] and others (n=6) [37,[39][40]42,44] (Table 1). A total of 249 individual study estimates were included among the 19 articles.…”
Section: Resultsmentioning
confidence: 99%
“…By stratifying based on the type of IBD, CD was signi cantly associated with an elevated risk of cervical cancer, while UC was not [27]. UC was increased the risk of thyroid cancer, while CD was not [29] (Fig. 3A-B).…”
Section: The Associations Between Ibd and Cancersmentioning
confidence: 99%
See 2 more Smart Citations